The influence of sleep health on dietary intake: a systematic review and meta‐analysis of intervention studies. Issue 2 (1st October 2020) - Fenton, S.; Burrows, T. L.; Skinner, J. A.; Duncan, M. J.
Abstract: Background: Poor dietary intake increases disease risk, and poor sleep influences diet. This systematic review and meta‐analysis of intervention studies aimed to evaluate the effect of sleep health on dietary intake in adults. Methods: Five online databases were used to identify studies published between 1970 and 2019. Included studies were interventions that modified sleep and reported dietary outcomes. Results: Fifty four full texts were assessed and 24 publications were included. Following risk of bias appraisal, data were narratively summarised and a sub‐group of studies ( n  = 15) was meta‐analysed to determine the effect of sleep on dietary intake. One intervention modified sleep timing and 23 modified duration. Sleep duration was partially restricted (≤5.5 h night –1 ) ( n  = 16), totally restricted ( n  = 4), partially and totally restricted ( n  = 1), and extended ( n  = 2). Dietary outcomes were energy intake ( n  = 24), carbohydrate, fat, protein intake ( n  = 20), single nutrient intake ( n  = 5), diet quality ( n  = 1) and food types ( n  = 1). Meta‐analysis indicated partial sleep restriction results in higher energy intake in intervention compared with control [standardised mean difference (SMD) = 0.37; 95% confidence interval (CI) = 0.21–0.52; P  < 0.001], with a mean difference of 204 kcal (95% CI = 112–295; P  < 0.001) in daily energy intake, and a higher percentage of energy from fat, protein, carbohydrate (fat: SMD = 0.33; 95% CI = 0.16–0.51; P  < 0.001; protein: SMD = 0.30, 95% CI = 0.12–0.47, P  = 0.001; carbohydrate: SMD = 0.22, 95% CI = 0.04–0.39, P  = 0.014). Conclusions: Partial sleep restriction with duration of ≤5.5 h day –1 increases daily energy intake, as well as fat, protein and carbohydrate intake. Further research is needed to determine the relationship between other dimensions of sleep health and dietary intake. Abstract : Poor dietary intake increases disease risk, and poor sleep influences diet. This systematic review and meta‐analysis aimed to evaluate the effect of sleep health on dietary intake in adults. Twenty‐four publications were identified. One intervention modified sleep timing and 23 modified duration. Meta‐analysis indicated partial sleep restriction (≤5.5 h) results in higher energy intake in intervention compared to control [standardised mean difference (SMD) = 0.37; 95% confidence interval (CI) = 0.21–0.52; P  < 0.001], with a mean difference of 204 kcal (95% CI = 112–295; P  < 0.001) in daily energy intake, and a higher percentage of energy from fat, protein, carbohydrate (fat: SMD = 0.33; 95% CI = 0.16–0.51; P  < 0.001; protein: SMD = 0.30, 95% CI =0.12–0.47, P  = 0.001; carbohydrate: SMD = 0.22, 95% CI = 0.04–0.39, P  = 0.014). Further research is needed to elucidate the relationship between other dimensions of sleep health and dietary intake.